Permanent challenge for a healthy environment - Marli Teresinha Gimeniz Galvão (Rev Rene)
For over a century, Florence Nightingale, a precursor of modern nursing, promulgated the importance of the adequate environment for disease prevention, treatment of diseased and their recovery. He highlighted, among others, the importance of clean air and environmental hygiene. Concerning the disease prevention, considered necessary care residences about air, water, sewerage, cleaning and illumination. In current times, the concepts expanded, the wounds arising from lack of water and sanitation, demonstrated care urgently in the wide mode environment, and prevention in the residential areas and peridomicile.